On the role of diffusivity ratio and partition coefficient in diffusional molecular transport in binary composite materials, with special reference to the Maxwell equation - Petropoulos, John H.; Papadokostaki, Kyriaki G.; Minelli, Matteo; Doghieri, Ferruccio (Journal of membrane science, 2014)
A criticism is offered in this paper of conclusions stated in two recent works [Marand and Surapathi, J. Membr. Sci. 415 (2012) 871; Singh et al., J. Membr. Sci. 448 (2013) 160] with reference to properties of composite materials which are relevant to the determination of steady state permeance of solute species. The discussion aims at clarifying conditions for the validity of “permeability models”, which claim for the role of the permeability ratio PA/PB in a binary composite of phases A and B, as the only parameter needed to estimate the overall relative effective permeability PM/PB, when size/shape distribution and arrangement of domains of the two phases are assigned. In this note, the thesis is rejected of a separate role for the solubility or partition coefficient in the performance of mixed matrix membranes and attention is driven to published numerical results which deserve to be revised. •Criticism is offered of questionable conclusions stated in recent papers about the subject.•Conditions for the applicability of “permeability models” are clarified.•Available simulation data are examined for consistency with conclusions stated.•Reassessment of results recently published on the subject.